THE ROLE OF TAHFIZH TEACHERS IN IMPROVING THE QUALITY OF LEARNING IN THE TAHFIZH QUR'AN ACCELERATION PROGRAM AT THE AR-ROIHAN INTEGRATED MADRASAH IBTIDAIYAH LAWANG MALANG - Hanis Ratnasari (EDUCATUM: Scientific Journal of Education, 2024)
Learning tahfizh Al-Qur'an is an essential thing to develop to produce the next generation of the nation which is based on the Al-Qur'an. Therefore, MIT Ar-Roihan Lawang Malang established the Qur'an Tahfizh Acceleration Program to accommodate students who want to focus on memorizing the Qur'an. Apart from that, the commitment of parents to be willing to accompany their Muroja'ah sons and daughters at home is also significant. Tahfizh learning for early childhood is a challenge for educators. Therefore, the role of Tahfizh Teachers is needed in improving the quality of Tahfizh learning. The aim of this research includes two problem formulations: 1) To describe the implementation of tahfizh Qur'an learning in the MIT Ar-Roihan Lawang Malang tahfizh Qur'an Acceleration Program 2) to describe the role of Tahfizh Teachers in improving the quality of tahfizh learning in the tahfizh Qur'an Acceleration Program at MIT Ar-Roihan Lawang Malang. This research uses a qualitative approach with an interactive case study type of research. Data collection uses interview, observation, and documentation techniques. Data analysis uses an interactive model (Miles, Huberman, and Saldana) which includes data condensation, data display, and conclusion. Check the validity of the data with credibility, transferability, dependability, and confirmability. The results of the research show that: 1) the implementation of tahfizh Qur'an learning in the MIT Ar-Roihan Lawang Malang Tahfizh Qur'an Acceleration Program includes: a) Tahfizh Teacher duties which include planning learning, implementing learning, and evaluating; b) The materials taught during tahfizh learning include memorizing the Qur'an, memorizing prayers, Tilawati, and Khot; c) Tahfizh learning methods which include the Talaqqi and Tasmi' methods; d) Tahfizh learning media which includes Tilawati teaching aids, blackboard, memorization material books, and murottal speakers; e) Tahfizh learning steps which include opening, muroja'ah, adding new memorization, students memorizing, depositing memorization, and closing; f) Evaluation of tahfizh learning which includes evaluating and assessing each memorization deposit, holding a pretest before carrying out munaqosah every time you complete memorizing one juz, and holding munaqosah, 2) the role of the Tahfizh Teacher in improving the quality of tahfizh learning in the Qur'an tahfizh Acceleration Program which includes the role teacher as: a) Administrator; b) Educator; c) Manager; d) Facilitator; e) Supervisor; f) Motivator; and f) Evaluator